Prepare for the Accuplacer Test with our comprehensive quiz featuring multiple choice questions, flashcards, hints, and explanations designed to enhance learning. Ace your exam and secure your academic future!

Practice this question and more.


Substitute x=3, y=-4, and z=2 into the equation 8 - 4(x - 1) = 2 + 3(4 - x). What is the resulting answer?

  1. -2

  2. 2

  3. 6

  4. 12

The correct answer is: -2

To solve the equation by substituting the given values of \( x \), \( y \), and \( z \), we start by replacing \( x \) with 3 in the equation \( 8 - 4(x - 1) = 2 + 3(4 - x) \). First, we substitute \( x = 3 \): 1. On the left side, calculate \( 8 - 4(3 - 1) \): - This becomes \( 8 - 4(2) \), which simplifies to \( 8 - 8 = 0 \). 2. On the right side, calculate \( 2 + 3(4 - 3) \): - This becomes \( 2 + 3(1) \), which simplifies to \( 2 + 3 = 5 \). Now the equation looks like \( 0 = 5 \), which clearly does not hold. However, since your selection was -2, it appears necessary to revisit the process of substituting correctly or possibly recalibrating the interpretation of the question since the computations directly show \( 0 = 5 \), indicating inconsistency given the input values. Therefore, it seems